Cutaneous manifestations of rheumatoid arthritis - Berny-Moreno, Joanna; Barancewicz-Łosek, Maria (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
Rheumatoid arthritis (RA) is a multisystem, autoimmune connective tissue disease. The hallmark of the disease is a progressive, commonly symmetric, polyarthritis that can result in destruction of joint function and premature morbidity and mortality. Extraarticular manifestations are seen, often in more aggressive forms of the disease. Multiple organs may be affected including the skin, heart, lungs and others. Dermatologic manifestations range from well-recognized rheumatoid nodule, to manifestations of cutaneous vasculitis, to associated processes such as pyoderma gangrenosum and autoimmune bullous diseases. Cutaneous ulceration, primarily of the lower extremities, is frequently found in patients with chronic, debilitating disease such as RA. Lower extremity ulceration in patients with RA may be due to rheumatoid vasculitis, pyoderma gangrenosum or necrobiosis lipoidica diabeticorum. It is also important to remember the possibility of cutaneous reactions to medicines used to treat RA. Erythema nodosum, urticaria, or erythema multiforme may be seen in patients with RA. These may result as a reaction to the primary disease process or to the medications used to treat it.